Archaeology of Medieval villages currently inhabited in Europe (Archaeopress archaeology., 2019)
Archaeological interventions in European rural settlements have largely focussed on villages abandoned during the last millennium. Most hamlets and villages of medieval origin remain inhabited, however, and excavations have been scarce. This book details excavations of inhabited sites in the UK, the Netherlands, France, Scandinavia and Spain.